The Effects of NO3− Supply on Mazzaella laminarioides (Rhodophyta, Gigartinales) from Southern Chile. (30th October 2014) - Navarro, Nelso P.; Figueroa, Félix L.; Korbee, Nathalie; Mansilla, Andrés; Matsuhiro, Betty; Barahona, Tamara; Plastino, Estela M.
Abstract The effects of nitrate supply on growth, pigments, mycosporine‐like amino acids (MAAs), C:N ratios and carrageenan yield were investigated in Mazzaella laminarioides cultivated under solar radiation. This species is economically important in southern Chile where an increase of nitrogen in coastal waters is expected as a consequence of salmon aquaculture activity. Apical segments were cultivated in enriched seawater with five different <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cqjrcv4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−</alternatives> concentrations (0, 0.09, 0.18, 0.38 and 0.75 mm) during 18 days. Although phycoerythrin and phycocyanin content, as well as C:N ratios, were reduced in the control treatment (without <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cqjrcwp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−</alternatives> supply), when compared to <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cqjrcx7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−</alternatives> treatments, total MAA concentration, carrageenan yield and growth rates were similar in all tested conditions. Nevertheless, during the experiment, an important synthesis of mycosporine‐glycine took place in a nitrate concentration‐dependent manner, with accumulation being saturated around 0.18 mm of nitrate. These results indicate that exposure to high <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cqjrczs" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−</alternatives> concentration of more than 100 times the values observed in the nature did not impair the photoprotection system, as determined by MAAs, nor did it have a deleterious effect on growth or carrageenan yield of M. laminarioides, a late successional species from Chile.